Cash Management DSS based on System Dynamics for MFIs (Global Journal of Management and Business Research, 2014)
All the institutions which share a commitment to serving clients with low-incomes that have been excluded from the formal banking sector are part of the microfinance industry. The Consultative Group to Assist the Poorest (the apex association of international donors who support microfinance) regards microfinance as "a powerful tool to fight poverty" that can help poor people to "raise income, build their assets, and cushion themselves against external shocks". Microfinance institutions (MFIs) have reached well over 100 million clients and achieved impressive repayment rates on loans. Because of the increase in the scale of operations, the concept and practice of microfinance have changed dramatically over the last decade and the microfinance is increasingly adopting a financial systems approach, either by operating on commercial lines or by systematically reducing reliance on interest rate subsidies and/or aid agency financial support.
Keywords: microfinance; decision support system; system dynamics; cash management